INCREASING MATHEMATICS LEARNING OUTCOMES THROUGH THE TEAMS GAMES TOURNAMENT MODEL IN CLASS III BANYUAJUH 2 ELEMENTARY SCHOOL - Wijining Tri Wulan Suci; Kusnaningsih Kusnaningsih; Rika Wulandari (maktab: Jurnal Pendidikan dan Teknologi, 2022)
Mathematics is one of the compulsory subjects taught at all levels of education. Even so, mathematics is still considered the most difficult subject in the minds of many students. One of the causes of this is the learning model used by the teacher is not in accordance with the characteristics of students. This research is a classroom action research that aims to determine the increase in mathematics learning outcomes through the application of the teams tournament model in class III SDN Banyuaju 2. Data collection in this study used data collection techniques in the form of interviews, observation, tests, and documentation with quantitative qualitative data analysis techniques. . The results of this study indicate that there is an increase in student learning outcomes in mathematics in each cycle. In cycle I, the average student learning outcomes reached a score of 68 with the percentage of students completing 50%. These results have not reached the target of success. Therefore, repetition of actions is carried out, in which the teacher in cycle II is more motivating and monitoring students during learning so that students are more focused. The results obtained were that the average score of students increased to 84 with the percentage of students completing 100%. This shows that the application of the teams games tournament model can improve student learning outcomes